2019
DOI: 10.3390/ijms20102398
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Ghrelin in Excessive Gestational Weight Gain—Association between Mothers and Offspring

Abstract: Two-thirds of pregnant women exceed gestational weight gain recommendations. Excessive gestational weight gain (EGWG) appears to be associated with offspring’s complications induced by mechanisms that are still unclear. The aim of this study was to investigate whether umbilical cord leptin (UCL) and ghrelin (UCG) concentrations are altered in full-term neonates born to EGWG mothers and whether neonatal anthropometric measurements correlate with UCL and UCG levels and maternal serum ghrelin and leptin as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 53 publications
3
18
0
6
Order By: Relevance
“…The results of two birth cohort studies found that excessive GWG correlated with greater leptin levels in either cord blood or post-delivery maternal serum [ 53 ]. Patro-Małysza et al [ 54 ] also reported greater umbilical cord leptin levels in neonates born to mothers with excessive GWG. Further, Vargas-Aguirre at al [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of two birth cohort studies found that excessive GWG correlated with greater leptin levels in either cord blood or post-delivery maternal serum [ 53 ]. Patro-Małysza et al [ 54 ] also reported greater umbilical cord leptin levels in neonates born to mothers with excessive GWG. Further, Vargas-Aguirre at al [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that the underlying cause of macrosomia can be disorders accompanying obesity, such as insulin resistance and hyper insulinemia as well as dysregulation of functioning of numerous neurohormones and cytokines, chronic inflammation, intensive oxidative stress, and epigenetic changes [ 1 , 45 , 48 ]. Among others, intensified placental transport of glucose and amino acids to the fetus and its higher mass were found in women and animals using a diet that favors obesity [ 45 , 49 , 50 , 51 ]. Changed transport of lipids in the placenta was found in obese women with GDM which can contribute to fetus overgrowth [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, birth weight was shown to be a determinant of umbilical cord ghrelin concentrations in infants [56]. In addition, a negative relation between ghrelin concentration in cord blood and head circumference was observed in girls but not boys in one study [55], in both in another report [53], while in a third study a positive correlation between cord blood ghrelin and head circumference was shown to be independent from sex [51]. In only boys and not girls, acyl ghrelin in the umbilical cord additionally correlated negatively with abdominal and thigh circumference [55].…”
Section: Umbilical Cordmentioning
confidence: 81%
“…While it was observed in one investigation that maternal plasma acyl ghrelin was higher than acyl ghrelin concentration in the cord blood [47], another study reported a contrary finding [48], and a third study found no difference between ghrelin concentration in the umbilical cord blood and in maternal serum [49]. Similarly inconsistent, one study found a positive [48], while other studies found no [50] or negative [51] correlation between umbilical cord ghrelin and maternal circulating levels. Lastly, total ghrelin levels were not correlated but acyl ghrelin were positively correlated between maternal and umbilical cord levels [47].…”
Section: Umbilical Cordmentioning
confidence: 92%
See 1 more Smart Citation